Comparative antimicrobial efficacy of herbal alternatives (Emblica officinalis, Psidium guajava), MTAD, and 2.5% sodium hypochlorite against Enterococcus faecalis: An in vitro study - Sandeep Dubey (Elsevier, 2016)
Aim: The objective of this study was to evaluate the antimicrobial efficacy of herbal alternatives (Emblica officinalis, Psidium guajava), BioPure MTAD, and 2.5% sodium hypochlorite against Enterococcus faecalis. Materials and method: The testing of the antimicrobial efficacy of selected medicaments against E. faecalis was done by the agar disk-diffusion method. Whatman paper discs of 6 mm diameter were prepared and soaked with the test solution. These discs were then placed onto the previously seeded agar Petri plates. Later, these plates were incubated for 48 h at 37 °C under the appropriate gaseous conditions in a CO2 incubator. A zone of inhibition was recorded in millimeter for each plate and the results were analyzed statistically. Result: MTAD was found to be superior in its antibacterial abilities against E. faecalis compared with the other irrigants used. All the other tested irrigants showed significant zone of inhibition. Conclusions: BioPure MTAD offers better antibacterial efficacy than NaOCl. E. officinalis and P. guajava are effective antibacterial agents against E. faecalis and can be used to reduce root canal microflora and root canal failures.